Data-driven investigation of ship fuel consumption integrating causal inference and hierarchical analysis - Wenjie Cao; Xinjian Wang; Wei Zhang; Huanhuan Li; Siming Fang; Zaili Yang (Transportation Research Part D: Transport and Environment, 2026)

Ultrasound-assisted complexation of Millettia speciosa by-product protein with polyphenols: improved structural properties, antioxidant and hypoglycemic activities, and gut microbiota modulation - Meng Wang; Jiexi Li; Feng Li; Yebao Chen; Fangfang Ban; Hua Yang; Siming Zhu; Dan Xu; Junlin Wu (Food Chemistry, 2026)

Dynamic modeling of submarine cable laying using ALE-ANCF: Insights into cable tension and configuration - Wenyan Gu; Xiangqian Zhu; Xinyu Li; Yanliang Pei; Jinsheng Zhang; Siming Yang; Zhixun Yang (Ocean Engineering, 2026)

Corrigendum to “A flood peak prediction in data-scarce mountain river basins considering the time distribution of rainfall” [J. Hydrol. 673 (2026) 135352] - Siming Li; Lu Chen; Binlin Yang; Bin Yi; Zhiyuan Leng; Tao Xie; Yang Song (Journal of Hydrology, 2026)

A flood peak prediction in data-scarce mountain river basins considering the time distribution of rainfall - Siming Li; Lu Chen; Binlin Yang; Bin Yi; Zhiyuan Leng; Tao Xie; Yang Song (Journal of Hydrology, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics” [Food Chem. 513 (2026) 149020] - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Changes in ginseng wine flavor characteristics during fermentation with Saccharomyces cerevisiae - Shen Yao; Yang Li; Xianwei Zeng; Yuan Cui; Zhaolian Li; Meichen Liu; Daqing Zhao; Shiting Yu; Siming Wang (Food Chemistry, 2026)

Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Screening and characterization of microbial consortia for biodegradation of high-salt and high-oil food waste - Meng Wang; Lirong Xia; Minghui Yang; Hua Yang; Zhongsheng Tang; Yebao Chen; Siming Zhu; Junlin Wu (Waste Disposal & Sustainable Energy, 2026)

Blade icing characteristics and dynamic response analysis of floating offshore wind turbine in cold marine environments - Haojie Zheng; Siming Zheng; Yang Yang; Koushik Kanti Barman; Gregorio Iglesias (Cold Regions Science and Technology, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Revealing long-term runoff mechanisms using the deep learning model interpretable framework driven by global and local information - Binlin Yang; Lu Chen; Siming Li; Bin Yi; Nengjie Hu (Journal of Hydrology, 2025)

Methionine in embryonic development: metabolism, redox homeostasis, epigenetic modification and signaling pathway - Chang Yan; Biyan He; Chenjun Wang; Wanzhen Li; Siming Tao; Jingqing Chen; Yuquan Wang; Ling Yang; Yingjie Wu; Zhenlong Wu; Ning Liu; Yinghe Qin (Critical Reviews in Food Science and Nutrition, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

Change detection in optical and SAR images by integrating fine-grained feature extraction and contextual transformation - Man Zhang; Liang Huang; Bohui Tang; Tonggen Yang; Siming Pu (Advances in Space Research, 2025)

A Dynamic Time-varying Distributed Unit Hydrograph Considering the Heterogeneity of Runoff Generation - Bin Yi; Lu Chen; Binlin Yang; Zhiyuan Leng; Siming Li; Tao Xie (Water Resources Management, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

An integrated non-alkaline derivatization strategy using 2,2′-dithiodipyridine and HPLC for simultaneous analysis of total and low-molecular-weight free thiols in human serum - Zhiyu Shao; Jie Zeng; Jun Dong; Fusui Ji; Hongxia Li; Ruiyue Yang; Wenxiang Chen; Wenyu Li; Siming Wang (Analytica Chimica Acta, 2025)

Germination and fermentation synergistically tailor the starch structure within brown rice and the quality features of brown rice tea - Yabin Guo; Yang Xu; Siming Zhao; Dongling Qiao; Bowen Li; Binjia Zhang (Food Research International, 2025)

Wheat bran insoluble fiber with varying particle distributions orchestrates microbial metabolism to counteract obesity and hyperlipidemia - Kexin Niu; Bingqian Yang; Lu Gan; Meng Niu; Kaikai Li; Siming Zhao (Food Bioscience, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Isolation and identification of native microalgae from the Yellow River Delta: A dual-focus study on the tolerance assessment of microalgae and their growth enhancement on Sesbania cannabina under saline-alkali stress - Xiao Yu; Siming Li; Jiahao Liang; Shenkun Liu; Yinchu Wang; Jianchao Yang; Chenggang Ren; Chunli Ji; Hongli Cui; Song Qin (Algal Research, 2025)

Integrative transcriptomic, proteomic and metabolomic analyses yields insights into muscle fiber type in cattle - Xiaofan Tan; Ruixue Zhao; Jing Chen; Zhiwei Yan; Xin Sui; Heling Li; Qiao Li; Xuehai Du; Yangzhi Liu; Siming Yao; Ying Yang; David M. Irwin; et al. (Food Chemistry, 2025)

Non-local μ(I) rheology improves landslide deposition modeling in MLS-MPM simulations - Shuxi Zhao; Yang Liu; Gianvito Scaringi; Xinpo Li; Siming He; Gang He; Lei Zhu (Engineering Geology, 2025)

Enhanced chitinase production by Bacillus paralicheniformis GXMU-J23.1: Optimization, genomic insights, and chitin degradation mechanism - Junjie Xie; Ligang Zhang; Kexin Yang; Hongyan Zhang; Mingguo Jiang; Siming Liao; Dengfeng Yang; Naikun Shen (Bioresource Technology, 2025)

Characteristics of Dissolved Inorganic Carbon (DIC) in the Western Coast of the Taiwan Strait Using a Shipboard Measurement - Jiehua Hu; Jinpei Yan; Hang Yang; Siming Huang; Siying Dai; Xiaoke Zhang; Shanshan Wang; Shuhui Zhao (Journal of Marine Science and Engineering, 2024)
An online dissolved inorganic carbon (DIC) monitoring system was produced to achieve high spatial and temporal resolution in DIC data from the western Taiwan Strait (WTS) during the summer. Surface seawater DIC, salinity, dissolved organic carbon (DOC), Chl-a, and NO3− samples were collected, as well as the vertical profiles of DIC, to understand DIC variations in the WTS. The results showed that the range of DIC levels in the surface seawater from the WTS was from 1.68 to 2.21 mmol/L (Mmol), with an average of 1.93 ± 0.19 Mmol, which was consistent with the sampling results using titration determination, with an average of 1.98 ± 0.12 Mmol. A high correlation (R2 = 0.96) was presented between the online monitoring and sampling detection of DIC, indicating that DIC could be measured with high accuracy using the online monitoring system. The spatial distribution of DIC was similar to that of salinity, but it was different from that of DOC and Chl-a. The DIC concentration positively correlated with salinity (R2 = 0.51) and presented a negative correlation (R2 = 0.92) with seawater temperature. However, the surface seawater DIC was almost independent from DOC and Chl-a in the observation sea areas. The DIC levels first increased and then decreased with the depth, with the highest DIC concentration occurring in the subsurface water at about 10 m, which was similar to the profiles of salinity and Chl-a in the northern and southern areas of the WTS. The profiles of DIC, salinity, NO3−, and Chl-a were almost independent from the water depth in the central WST. This indicated that seawater DIC in the WTS was mainly affected by seawater temperature, salinity, and the vertical mixing of sea water, but it was less impacted by TOC and Chl-a.

Effects of microplastics separate exposure and co-exposure to 17β-estradiol on the productive performance of juvenile female Chinese mitten crab (Eriocheir sinensis) - Yang Fu; Jian Zhang; Yilong Cui; Bo Li; Siming Huo; Jiayu Du; Yanfei Li (Science of The Total Environment, 2024)

Untargeted metabolomics to detect and identify plasma metabolic signatures associated with intracranial aneurysm and its rupture - Siming Gui; Jia Jiang; Dingwei Deng; Dachao Wei; Xiheng Chen; Yudi Tang; Jian Lv; Wei You; Ting Chen; Yang Zhao; Hengwei Jin; Xinke Liu; et al. (Metabolic Brain Disease, 2024)

Evaluating the impact of improved filter-wrapper input variable selection on long-term runoff forecasting using local and global climate information - Binlin Yang; Lu Chen; Bin Yi; Siming Li (Journal of Hydrology, 2024)

The toxic effects and mechanisms of maternal exposure to Bisphenol F during gestation and lactation on lungs in female offspring mice - Jiayu Du; Siming Huo; Bo Li; Xuliang Zhang; Jian Zhang; Yang Fu; Bing Shao; Yanfei Li; Miao Song (Environmental Pollution, 2024)

CO prodrugs: a new scaffold of adamantane-fused norbornen-7-ones with tunable water solubility - Ce Yang; Xingyue Ji; G. S. Sainaga Jyothi Vaskuri; Xiaoxiao Yang; Wen Lu; Zhengnan Yuan; Dongning Liu; Siming Wang; Chalet Tan; Binghe Wang (Medicinal Chemistry Research, 2024)

Dynamic modeling of cable deployment/retrieval based on ALE-ANCF and adaptive step-size integrator - Siming Yang; Hui Ren; Xiangqian Zhu (Ocean Engineering, 2024)

Advancements and future perspectives in the study of oligosaccharides derived from edible-medicinal mushrooms - Shuo Wang; Jiajie Qi; Xiaoming Cai; Weijie Wu; Zhuo A. Wang; Siming Jiao; Caihong Dong; Yi Li; Zhenquan Yang (Food Bioscience, 2024)

Experimental study on human evacuation onboard passenger ships considering heeling angle and opposite directions - Siming Fang; Zhengjiang Liu; Xinjian Wang; Ben Matellini; Jin Wang; Zaili Yang; Xinyu Zhang; Bo Wan; Shengke Ni (Ocean Engineering, 2024)

A two-dimensional σ-transform based finite element method for nonlinear water waves - Siming Yang; Xiangqian Zhu; Hui Ren (Ocean Engineering, 2024)

MPM simulation of frictional heating–induced hypermobility of landslides - Xiaoqin Lei; Siming He; Xiaoqing Chen; Zongji Yang; Youkou Dong; Liangliang Wang (Landslides, 2024)

Investigating the dynamic process of a rock avalanche through an MLS-MPM simulation incorporated with a nonlocal μ(I) rheology model - Shuxi Zhao; Siming He; Xinpo Li; Gianvito Scaringi; Yang Liu; Yu Deng (Landslides, 2024)

A numerical method to consider the interaction between multiple fractures in frozen rocks based on XFEM - Yun Zhou; Xianjun Tan; Diansen Yang; Weizhong Chen; Zhouzhou Su; Peichao Zheng; Reziwanguli Shataer; Dong Wang; Siming Tian; Wei Wang (Computers and Geotechnics, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

The hepatotoxicity of hexafluoropropylene oxide trimer acid caused by apoptosis via endoplasmic reticulum-mitochondrial crosstalk - Jiayu Du; Xuliang Zhang; Bo Li; Siming Huo; Jian Zhang; Yang Fu; Miao Song; Bing Shao; Yanfei Li (Science of The Total Environment, 2024)

Biodegradable copper peroxide decorated hollow polydopamine nanocomposite as effective chloroperoxidase delivery carrier for enhancing enzyme dynamic therapy via self-activated cascade reactions - Weiwei Wu; Yan Yang; Yu Zhang; Yina Zeng; Zhuoying Liang; Xiling Song; Yadong Huang; Wei Xue; Siming Yu (Chemical Engineering Journal, 2024)

A 26-week repeated dose toxicity evaluation of sporoderm-removed Ganoderma lucidum spores in rats - Lijuan Xia; Ruimin Sun; Liyan Zhang; Jinrong Li; Chengda Zhang; Qian Yang; Lili Zhang; Siming Zhang; Hanbo Wang; Hanying Lyu; Wanqiang Lyu; Zhenhao Li; et al. (Food and Chemical Toxicology, 2023)

A quantitative study of the factors influencing human evacuation from ships - Siming Fang; Zhengjiang Liu; Xihan Yang; Xinjian Wang; Jin Wang; Zaili Yang (Ocean Engineering, 2023)

Kif15 deficiency contributes to depression-like behavior in mice - Junpei Wang; Qifeng Tu; Siming Zhang; Xiaomei He; Chao Ma; Xiaowei Qian; Ronghua Wu; Xinyu Shi; Zhangyi Yang; Yan Liu; Zhangji Dong; Mei Liu (Metabolic Brain Disease, 2023)

Dynamic analysis of a deep-towed seismic system based on a flexible multi-body dynamics frame - Siming Yang; Xiangqian Zhu; Hui Ren (Ocean Engineering, 2023)

Metagenomic insights into the inhibitory mechanisms of Cu on fermentative hydrogen production - Jinman Cao; Guilan Duan; Aijun Lin; Yaoyu Zhou; Siming You; Jonathan W.C. Wong; Guang Yang (Bioresource Technology, 2023)

Aspergillus sp. R3, a new producer for cyclopyazonic acid, inhibits rice sheath blight fungus Rhizoctonia solani Kühn - Xiangyu Qin; Yuanhang Chang; Yao Wang; Jie Yang; Siming Nie; Na Guo; Jian Xu; Fengkun Cai; Chunjian Zhao; Yujie Fu (Physiological and Molecular Plant Pathology, 2023)

Substratum virtualization in three-dimensional landslide modeling with the material point method - Shuxi Zhao; Lei Zhu; Wei Liu; Xinpo Li; Siming He; Gianvito Scaringi; Xiong Tang; Yang Liu (Engineering Geology, 2023)

Reconstruction of dynamics processes of Tagharma rock avalanche in Pamir Plateau: Geomorphology and sedimentology implications - Lei Zhu; Siming He; Xiaoqin Lei; Zongji Yang; Jihao Jian; Yi Zhang; Yong Wu; Jiang Li (Engineering Geology, 2023)

Genetic parameters for growth and Quambalaria shoot blight resistance in Corymbia citriodora subsp. variegata - Shengkan Chen; Jianbo Chen; Guanming Yi; Mei Qin; Shiqi Ren; Ziyu Deng; Qinglan Tang; Dongqiang Guo; Yuanli Zhu; Zhangqi Yang; Chonglu Zhong; Siming Gan; et al. (Euphytica, 2021)

Modeling the landslide-generated debris flow from formation to propagation and run-out by considering the effect of vegetation - Wei Liu; Zongji Yang; Siming He (Landslides, 2021)

Single-cell transcriptome analysis of the novel coronavirus (SARS-CoV-2) associated gene ACE2 expression in normal and non-obstructive azoospermia (NOA) human male testes - Xixi Liu; Yidong Chen; Wenhao Tang; Li Zhang; Wei Chen; Zhiqiang Yan; Peng Yuan; Ming Yang; Siming Kong; Liying Yan; Jie Qiao (Science China Life Sciences, 2020)

Photocatalytic removal of elemental mercury via Ce-doped TiO2 catalyst coupling with a novel optical fiber monolith reactor - Feng Xin; Siming Ma; Jianping Yang; Yongchun Zhao; Junying Zhang; Chuguang Zheng (Environmental Science and Pollution Research, 2020)

Measuring and estimating the impact pressure of debris flows on bridge piers based on large-scale laboratory experiments - Dongpo Wang; Zheng Chen; Siming He; Yang Liu; Hao Tang (Landslides, 2018)

Genotypic Variation and Genotype-by-Environment Interactions in Growth and Wood Properties in a Cloned Eucalyptus urophylla × E. tereticornis Family in Southern China - Heyu Yang; Qijie Weng; Fagen Li; Changpin Zhou; Mei Li; Shengkan Chen; Hongxia Ji; Siming Gan (Forest Science, 2018)

Emission controls of mercury and other trace elements during coal combustion in China: a review - Yongchun Zhao; Jianping Yang; Siming Ma; Shibo Zhang; Huan Liu; Bengen Gong; Junying Zhang; Chuguang Zheng (International Geology Review, 2018)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Fibroblast growth factor (FGF21) protects mouse liver against d-galactose-induced oxidative stress and apoptosis via activating Nrf2 and PI3K/Akt pathways - Yinhang Yu; Fuliang Bai; Yaonan Liu; Yongbi Yang; Qingyan Yuan; Dehua Zou; Susu Qu; Guiyou Tian; Liying Song; Tong Zhang; Siming Li; YunYe Liu; et al. (Molecular and Cellular Biochemistry, 2015)

Dissimilar characteristics of umbilical cord mesenchymal stem cells from donors of different ages - Sha Huang; Changjiang Feng; Yan Wu; Siming Yang; Kui Ma; Xu Wu; Xiaobing Fu (Cell and Tissue Banking, 2013)

Molecular and expression analysis of manganese superoxide dismutase (Mn–SOD) gene under temperature and starvation stress in rotifer Brachionus calyciflorus - Jianghua Yang; Siming Dong; Huanxi Zhu; Qichen Jiang; Jiaxin Yang (Molecular Biology Reports, 2013)

Antibody-Mediated Inhibition of Integrin α5β1 Blocks Neurotoxic Prion Peptide PrP106–126-Induced Activation of BV2 Microglia - Jiaxin Chang; Lifeng Yang; Mohammed Kouadir; Yun Peng; Siming Zhang; Fushan Shi; Xiangmei Zhou; Xiaomin Yin; Deming Zhao (Journal of Molecular Neuroscience, 2012)